2016
DOI: 10.1159/000444248
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes-Enriched Hemodiafiltration Solutions for Continuous Renal Replacement Therapy in Acute Kidney Injury: A Crossover Study

Abstract: Aims: To evaluate the capability of an electrolytes-enriched solution to prevent metabolic disorders during continuous veno-venous hemodiafiltration (CVVHDF). Methods: Serum biochemistry and clinical tolerance were compared during CVVHDF treatments with an electrolyte-enriched (Phoxilium) or standard solutions in 10 acute renal failure patients. Results: As compared to standard fluids, serum potassium and phosphate levels were maintained in the normal range with Phoxilium without any supplementation but total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…Hypokalemia can also develop during CRRT, although its incidence is lower than that of hypophosphatemia. Several recent studies have investigated the usefulness of phosphate-and potassium-containing dialysis solution [16,17,20,21]. Broman et al reported that phosphate-containing replacement and dialysis solutions reduced variability in serum phosphate levels during CRRT and the incidence of hypophosphatemia [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypokalemia can also develop during CRRT, although its incidence is lower than that of hypophosphatemia. Several recent studies have investigated the usefulness of phosphate-and potassium-containing dialysis solution [16,17,20,21]. Broman et al reported that phosphate-containing replacement and dialysis solutions reduced variability in serum phosphate levels during CRRT and the incidence of hypophosphatemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Broman et al reported that phosphate-containing replacement and dialysis solutions reduced variability in serum phosphate levels during CRRT and the incidence of hypophosphatemia [17]. In a crossover study, Noemie et al reported that phosphate-and potassium-containing solution prevented hypophosphatemia and hypokalemia during CVVHDF [20].…”
Section: Discussionmentioning
confidence: 99%
“…During CRRT, commercially available dialysates and replacement fluids in Japan can cause hypokalemia and hypophosphatemia, and the latter is reported to delay weaning from mechanical ventilation; therefore, appropriate supplementation of potassium and/or phosphate through intravenous or enteral nutrition can be beneficial [ 196 , 211 213 ]. Outside of Japan, a CRRT dialysate containing 4.0 mEq/L potassium and 3.7 mg/dl phosphorus has been developed [ 214 ]. However, a switch from CRRT to intermittent renal replacement therapy (IRRT) can easily cause an electrolyte imbalance, thereby calling for a reexamination of the content of the intravenous nutrition or enteral nutrition, including the total fluid volume; in particular, the risk of hyperkalemia must be kept in mind.…”
Section: Commentarymentioning
confidence: 99%
“…During CRRT, commercially available dialysates and replacement fluids in Japan can cause hypokalemia and hypophosphatemia, and the latter is reported to delay weaning from mechanical ventilation; therefore, appropriate supplementation of potassium and/or phosphate through intravenous or enteral nutrition can be beneficial [ 194 , 209 211 ]. Outside of Japan, a CRRT dialysate containing 4.0 mEq/L potassium and 3.7 mg/dL phosphorus has been developed [ 212 ]. However, a switch from CRRT to intermittent renal replacement therapy (IRRT) can easily cause an electrolyte imbalance, thereby calling for a reexamination of the content of the intravenous nutrition or enteral nutrition, including the total fluid volume; in particular, the risk of hyperkalemia must be kept in mind.…”
Section: Cq6-4: What Nutritional Support Is Recommended For Aki Treatmentioning
confidence: 99%